Enhancing Bangla video comprehension through multimodal feature integration and attention-based encoder-decoder captioning models for single-action videos - Das, Saurav; Biswas, Shammo; Fahim, Taimoor; Sanjan, M.A.B. Siddique; Tarannum, Tasnia Alam (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.